Improving the Quality of Sago Pith and Rumen Content Mixture as Poultry Feed Through Fermentation by Bacillus amyloliquefaciens - Wizna; Abbas, Hafil; Rizal, Yose; Dharma, Abdi; Kompiang, I. Putu (Pakistan Journal of Nutrition, 2008)
An experiment was conducted to improve the nutrient content of sago pith (Metroxylon sago Rottb) and rumen content mixture through fermentation by using cellulolytic bacteria (Bacillus amyloliquefaciens) as inoculums. The experiment was determination of the optimum conditions (dosage of inoculums, fermentation length and temperature) for sago pith and rumen content mixture fermentation based on nutrient quality and quantity of these fermented products. The study was conducted in experimental methods, using the completely randomize design in factorial with 3 treatment were : 1. A factor (Dosage of inoculums: A1 = 2%, A2 = 6%, A3 = !0%), 2. B factor (Fermentation length : B1 = 3 days, B2 = 6 days, B3 = 9 days) and 3. C factor (Temperature : C1 = 30oC, C2 = 40oC and C3 = 50oC). Results of study showed that optimum conditions of the fermentation of sago pith (Metroxylon sago Rottb) and rumen content mixture was at 2% dosage of inoculums, 9 days of fermentation length and 40oC temperature. This conditions can decrease 33% of crude fiber and increase 42% of crude protein which made the nutritional value of the product based on dry-substance was 15.79% crude protein, 2.75% crude fat, 18.54% crude fiber, 0.20% calcium, 0.16% phosphor, 2540 Kcal/kg metabolic energy, and 66.65% nitrogen retention.